Effects of selected pre-treatment methods on the hydration behaviour of rattan-cement mixtures (2010)
"The influence of clacium chloride (CaCl2), magnesium chloride (MgCl2), hot-and cold-water pre-treatments, and prolonged storage on the hydration behaviour of particles extracted from Calamus deerratus and Laccosperma secundiflorum rattan canes mixed with cement was investigated. While the untreated rattans inhibited cement setting, pre-treatments generally improved compatibility.The addition of chemical additives and aquenous pre-treatments enhanced the compatibility of the rattan-cement composites while peeling of silicified epidermis generally reduced the compatibility parameters. Pre-storage positively influenced the hydration behaviour of the L.secundiflorum composites while it negatively affected the Calamus composites. Statistical analyses revealed that all the pre-treatment methods employed significantly improved the hydration behaviour of the rattan-cement mixes except water and CaCl2 treatments. The compatibility indices based on the maximum hydration temperature (Tmax),compatibility factor (CA), setting time (tmax) and time ratio indices (tR) did not consistently predict the hydration behaviour of the rattan composites. A modified time ratio index based on the threshold temperature (40oC) is proposed for prediction of the hydration behaviour of rattan-cement mixes "